ANALISIS PENTINGNYA LITERASI DIGITAL BERBASIS E-BOOKLET BAGI GURU SD KELAS V DI SDN SUNGAI ANDAI 4 DALAM MENGAJARKAN MATA PELAJARAN BAHASA INDONESIA DI ERA DIGITAL - Tutwuri Handayani, Silvi; Cahyani, Irni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The integration of digital technology into elementary education requires teachers to possess adequate digital literacy skills. However, the use of e-booklets in Indonesian language learning remains limited. This study aimed to analyze the importance of e-booklet-based digital literacy for fifth-grade teachers at SDN Sungai Andai 4. A qualitative descriptive approach was employed using observation, interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that e-booklet-based digital literacy helps teachers deliver learning materials more systematically and attractively, increasing students' motivation and engagement in Indonesian language learning. However, limitations in technological facilities, internet access, and teachers' digital competencies remain challenges. Therefore, improving teachers' digital literacy through continuous training and adequate technological support is essential to optimize the use of e-booklets in elementary education.